Application of Functionals in Creating Inequalities - Zlatko Pavić; Shanhe Wu; Vedran Novoselac (Journal of Function Spaces)
The paper deals with the fundamental inequalities for convex functions in the bounded closed interval. The main inequality includes convex functions and positive linear functionals extending and refining the functional form of Jensen’s inequality. This inequality implies the Jensen, Fejér, and, thus, Hermite-Hadamard inequality, as well as their refinements.